Development strategy for smallholder oil palm and coconut plantation in Pesisir Selatan Regency - Hetty Novita Agus; Andrea Emma Pravitasari; Supijatno (Journal of the Saudi Society of Agricultural Sciences)
Abstract This study aims to formulate development strategies for smallholder oil palm and coconut commodities in Pesisir Selatan Regency, West Sumatera Province, using the A'WOT method, which combines the Analytic Hierarchy Process (AHP) and SWOT (Strengths, Weaknesses, Opportunities, Threats). AHP assigns weights and prioritises factors identified in the SWOT analysis, which evaluates the strengths, weaknesses, opportunities, and threats of developing both commodities. The findings reveal that the primary strategy for oil palm development focuses on adopting technology to improve production efficiency and quality while reducing dependence on intermediaries. For coconut, the primary strategy emphasises government support for plantation replanting programs and establishing value-added processing industries to enhance farmers' economic growth. The study also highlights the importance of integrating sustainability practices and aligning with global agricultural development goals. The practical implications of these findings suggest that implementing strategies involving technological support, plantation replanting, and value-added processing can enhance the competitiveness and sustainability of both commodities in Pesisir Selatan. These strategies are expected to serve as a model for other regions in Southeast Asia, promoting sustainable agriculture, improving farmers' livelihoods, and strengthening economic resilience.